Perancangan Interior Kantor Outsourcing dengan Penerapan Konsep Smart Office di Surabaya - Sherenna Imanuele Finanta; Sherly de Yong; Lucky Basuki (Intra, 2019)
Outsourcing office is an office that provides labor distribution services. In the outsourcing office interactions happens from various parties, from office employees and company users to job applicants. In Surabaya, the outsourcing office facilities are still not integrated, resulting in less optimal service convenience. Basically, services formed when interaction happens between customers and service providers (This Is Service Design Thinking, p.36). Methods used in the design is Service Design Thinking which consists of 4 stages, they are exploration, creation, reflection and implementation. There are many tools in the method, some of which are customer journey maps, storyboards, canvas business models, and service blueprints. The use of the smart office concept emphasizes integrated office interior design and efficiency of space users, especially facilities and touchpoints for them. The design will benefits office employees, company users and job applicants to recognize the existence of an integrated office outsourcing service system through interior facilities for the convenience of employees.